AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN, BATANG, DAN AKAR KENIKIR (COSMOS CAUDATUS KUNTH.) DENGAN METODE DPPH DAN CUPRAC - Saryani, Resti
Free radicals are molecules that release one electron from their partner's electrons to become reactive. Antioxidant can scavenge the reactive properties of free radicals. Antioxidants can be found in various plants, one of which is wild cosmos (Cosmos caudatus Kunth.). The objectives of this research were to study antioxidant activity of leaves, stems, and roots of wild cosmos by DPPH (2,2-diphenyl-1- picrylhydrazyl) and CUPRAC (Cupric Ion Reducing Antioxidant Capacity) methods; determine total phenolic and flavonoid content, analyze the correlation between total phenolic and flavonoid content with antioxidant activity, and correlation of two methods were tested by Pearson’s method. Extraction was carried out by reflux method using increasing polarity solvent e.g. n-hexane, ethyl acetate, and ethanol. Determination of IC50 of DPPH, EC50 of CUPRAC, total phenolic and flavonoid content using UV -visible spectrophotometry. The IC50 of DPPH of leaves, stems, and roots extracts of wild cosmos were in the range of 5.93-102.21 ?g/mL, while EC50 of CUPRAC 40.06-693.65 ?g/mL. The highest total phenolic content was given by ethanol leaves extract of wild cosmos (12.90 ± 0.32 g GAE/100 g) and the highest flavonoid content was given by ethyl acetate leaves extract of wild cosmos (9.82 ± 0.61 g QE/100 g). Phenolic content had negative and significant correlation with IC50 of DPPH of leaves and stems extract of wild cosmos. Total phenol also had negative and significant correlation with EC50 of CUPRAC of leaves extract of wild cosmos. The IC50 of DPPH of leaves extract had positive and significant correlation to EC50 of CUPRAC. The ethyl acetate and ethanol extract of leaves, stems, and roots of wild cosmos can be classified as very strong antioxidant by the DPPH method. Phenolic compounds were the main contributor in antioxidant activities of leaves and stems extracts by DPPH method and main contributor in leaves extract using CUPRAC method. The DPPH and CUPRAC methods gave linear results in antioxidant activity of leaves extract of wild cosmos.